Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s41030-020-00121-w
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Asthma in Elderly Japanese Patients: Using Hospital-Based Administrative Claims Data

Abstract: Introduction: Data are lacking on severe asthma burden in elderly people in Japan. We assessed the prevalence and clinical/economic burden of severe asthma and asthma-related hospitalizations in elderly and younger Japanese patients. Methods: This retrospective study analyzed outpatient claims data and inpatient hospital discharge records among patients aged C 15 years with asthma (defined as C 2 prescriptions of inhaled corticosteroids [ICS] or ICS/long-acting beta-agonists [LABA]) between 1 July 2014 and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Data on SCS use in Japan were obtained from two claims analyses previously described. In the larger study ( n = 35,742), 31.1% of patients with severe asthma used SCS as daily maintenance therapy, with a mean cumulative exposure of 847 mg/year 44 . Data from the KEIFU study revealed that, over a 12‐month period, SCS were prescribed to 67.4% of patients with SUA, 45.9% with SCA and 16.2% with mild‐to‐moderate asthma at mean daily cumulative exposures of 3.3 mg (1.2 mg via injection), 1.6 and 0.2 mg, respectively.…”
Section: Asthma Severity and Scs Usage In Asiamentioning
confidence: 98%
See 3 more Smart Citations
“…Data on SCS use in Japan were obtained from two claims analyses previously described. In the larger study ( n = 35,742), 31.1% of patients with severe asthma used SCS as daily maintenance therapy, with a mean cumulative exposure of 847 mg/year 44 . Data from the KEIFU study revealed that, over a 12‐month period, SCS were prescribed to 67.4% of patients with SUA, 45.9% with SCA and 16.2% with mild‐to‐moderate asthma at mean daily cumulative exposures of 3.3 mg (1.2 mg via injection), 1.6 and 0.2 mg, respectively.…”
Section: Asthma Severity and Scs Usage In Asiamentioning
confidence: 98%
“…43 An analysis of hospital-based administrative claims for 35,742 outpatients from July 2014 to June 2017 in Japan revealed that 11.8% of patients with asthma had severe disease, comprising 8.2% of patients aged 15-39 years, 12.8% of those aged 40-64 years, and 12.4% of those aged ≥65 years. 44 Also in Japan, a health insurance claims analysis for 10,579 patients from 2014 to 2015 (KEIFU study) revealed that 7.8% had severe asthma, 2.5% had severe uncontrolled asthma (SUA) and 5.3% had severe controlled asthma (SCA). 45 In South Korea, a national, population-based study that evaluated data by year from 2002 (n = 597,344) to 2015 (n = 1,130,530) reported an increase in overall asthma prevalence from 1.6% to 2.2% and in severe asthma from 3.5% to 6.1% over that time.…”
Section: Asthma Prevalence Severity and Control In Asiamentioning
confidence: 99%
See 2 more Smart Citations
“… 3 An understanding of EA is critical; it imposes considerable burdens in terms of mortality and morbidity, and expenditure. 4 5 6 7 However, clinicians lack knowledge of EA and thus often prescribe inappropriate management. In this review, we ask 3 key questions frequently encountered during EA diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%